Inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase by mevinolin in familial hypercholesterolemia heterozygotes: effects on cholesterol balance. - Grundy, S M (1984)
Patients with heterozygous familial hypercholesterolemia (FH) have a deficiency of receptors for plasma low-density lipoprotein (LDL) that impairs removal of LDL from plasma. In these patients, mevinolin, an inhibitor of 3-hydroxy-3-methylglutaryl-CoA reductase [mevalonate:NAD+ oxidoreductase (CoA-acylating), EC 1.1.1.88], increases receptors for LDL and decreases LDL concentrations. To determine whether mevinolin also causes severe decreases in total body synthesis of cholesterol, fecal excretions of neutral steroids and acidic steroids were determined in five FH heterozygotes before and during treatment with mevinolin. The drug produced an average decrease in plasma total cholesterol of 23% and in LDL cholesterol of 24%. Mevinolin caused a significant decrease in the output of neutral and acidic steroids in three patients, but it caused no alterations in two others. Changes in fecal output of steroids did not correlate with the degree of lowering of the patients' LDL-cholesterol level. In none of the patients did the output of fecal steroids fall below the values seen in normal subjects studied under similar conditions. One patient had a previous ileal exclusion operation and had a massive output of acidic steroids in the control period; mevinolin therapy caused a slight decrease in excretion of acidic steroids, but the output was still markedly above normal. We conclude that the LDL lowering action of mevinolin does not appear to require a severe decrease in cholesterol synthesis that might lead to depletion of vital body stores of cholesterol.